A new finite strip formulation based on Carrera unified formulation for the free vibration analysis of composite laminates. Issue 26 (26th October 2022) - Daraei, Behnam; Shojaee, Saeed; Hamzehei-Javaran, Saleh
Abstract: In this article, a new finite strip formulation based on Carrera unified formulation (CUF) is developed to perform the free vibration analysis of cross- and angle-ply composite laminated plates. The FSM discretizes the plate by a number of strips which are connected through the nodal lines, and calls for use of simple polynomial shape functions in one direction of the plane of strips and harmonic series in the other. In the present formulation, all three components are considered for displacement field in each nodal line. CUF approach which is obtained in the framework of the Carrera unified formulation, permits stating the unknown variables as a set of the function expansions depending on the thickness coordinate and the corresponding variable depending on the in-plane coordinates. Several numerical examples for the analysis of laminated plates are presented and the effect of the number of strips, order of expansion, different relative thickness ratio and various boundary conditions are demonstrated.